MicroRNA-125b predicts clinical outcome and suppressed tumor proliferation and migration in human gallbladder cancer - Liang Yang; Sheng Huang; Hongbin Ma; Xiaoxiong Wu; Feiling Feng (Tumor Biology)
We intended to investigate the functional role and clinical relevance of microRNA-125b in human gallbladder cancer. Quantitative real-time polymerase chain reaction was used to examine microRNA-125b expression in gallbladder cancer cell lines, and 79 pairs of gallbladder cancer and normal gallbladder clinical tissues. Clinical correlations between tumorous microRNA-125b expression and gallbladder cancer patients’ clinicopathological variances or overall survivals were statistically analyzed. In gallbladder cancer cell lines, TYGBK-8 and G-415 cells, microRNA-125b was upregulated to examine its regulatory effect on gallbladder cancer proliferation and migration in vitro. MicroRNA-125b was significantly downregulated in gallbladder cancer cell lines and human gallbladder cancer tumors. MicroRNA-125b in gallbladder cancer was significantly correlated with patients’ clinical stage, tumor differentiation, lymph metastasis, and tumor invasion. Low tumorous microRNA-125b expression was also found to be associated with poor overall survivals among gallbladder cancer patients. In vitro studies demonstrated that microRNA-125b upregulation significantly suppressed proliferation and migration in TYGBK-8 and G-415 cells. Tumorous microRNA-125b is an independent prognostic biomarker for patients with gallbladder cancer and possibly acts as a tumor suppressor in gallbladder cancer.